The possibilities of evaluating the yield strength in the heat affected zones of a weld through indentation - Hanus, Petr; Schmidová, Eva (Trans Tech Publications, 2016)
The research focuses on elastic-plastic behaviour of welded joints of materials which are commonly used in both constructional practice and the automotive industry. The examined welded joints are oriented to a common constructional S355 and a modern high-strength steel DOMEX 700MC. The main tool for the assessment of the elastic-plastic response was the methodology based on the instrumented penetration testing with the use of a cylindrical indenter. The indentation tool was applied into narrow zones of welded boundaries. These zones represent critical areas of welded constructions because of a changing structure and different mechanical properties than the basic material possesses. The indentation data were recalculated to the mechanical properties in shear with the help of Hencky´s hypotheses about material behaviour. The correctness of the used methodology was verified by a tensile test. The aim of the work is to determine optimal methods for defining a yield strength and to find a hardening trend in the zones. The comparison of these steels revealed different changes due to the welding process. A substantial decrease of the yield strength of Domex700MC was observed, as a contrary to a stable, or partially increased, yield strength of the S355 steel. Structural analyses revealed a different material response of the evaluated steels, according to a different hardness in the heat affected zone.
Možnosti vyhodnocování meze kluzu pomocí indentační metody v tepelně ovlivněných zónách svaru
Keywords: mechanical properties; indentation method; microstructures; hardness; tensile test; mechanické vlastnosti; indentační metoda; mikrostruktura; tvrdost; tahová zkouška